Derived Time in Range and Other Metrics of Poor Glycemic Control Associated With Adverse Hospital Outcomes in Patients With Diabetes Mellitus Admitted to Non-ICU Wards at a Tertiary-Level Hospital in Colombia: A Cross-Sectional Study - Edwin Mora Garzón; Alexandra González Montoya; Gilma Hernández Herrera (Journal of Diabetes Research)
Conclusion: A significant number of hospitalized diabetic patients exhibit poor glycemic control, which has been found to be associated with adverse outcomes, including increased mortality. Metrics like dTIR and glycemic variability should be considered as targets for glycemic control, highlighting the need for enhanced management strategies.